2021
DOI: 10.1002/eji.202149175
|View full text |Cite
|
Sign up to set email alerts
|

IL‐33/ST2 as a potential target for tumor immunotherapy

Abstract: IL‐33, a member of the IL‐1 family, was initially reported to be expressed constitutively in the nucleus of tissue‐lining and structural cells. However, upon tissue damage or injury, IL‐33 can be released quickly to bind with its cognate receptor ST2 in response to wound healing and inflammation and act as a DAMP. As a key regulator of Th2 responses, IL‐33/ST2 signal is primarily associated with immunity and immune‐related disorders. In recent years, IL‐33/ST2 signaling pathway has been reported to promote the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 122 publications
(187 reference statements)
0
20
0
Order By: Relevance
“…Incidentally, AstraZeneca is conducting the trial of a monoclonal antibody called MEDI3506 (anti-IL-33) in patients with diabetic nephropathy. However, this trial has not yet been completed (Jiang et al, 2021). It is known that the main side effect of monoclonal antibody administration is the risk of an adverse immune response (Hansel et al, 2010;Liu and Li, 2014).…”
Section: The Potential Value Of the Il-33/ St2 Pathway For Renal Fibrosismentioning
confidence: 99%
“…Incidentally, AstraZeneca is conducting the trial of a monoclonal antibody called MEDI3506 (anti-IL-33) in patients with diabetic nephropathy. However, this trial has not yet been completed (Jiang et al, 2021). It is known that the main side effect of monoclonal antibody administration is the risk of an adverse immune response (Hansel et al, 2010;Liu and Li, 2014).…”
Section: The Potential Value Of the Il-33/ St2 Pathway For Renal Fibrosismentioning
confidence: 99%
“…IL‐33 exert both protumor and antitumor effects, depending mainly on the host's tumor immune microenvironment, but also on the tissue source of IL‐33. In general, IL‐33 of tumor tissue origin exerts antitumor effects by promoting the local aggregation of NK cells, CD8+ T cells, ILC2 and eosinophils in the tumor, whereas IL‐33 of tumor stromal cell origin exerts protumor effects by promoting the local aggregation of Tregs and MDSCs in the tumor 52,53 . The study demonstrated that IL‐33 expression in cytoplasm of tumor was significantly and positively correlated with CD3 + /CD8 + T lymphocytes.…”
Section: Discussionmentioning
confidence: 89%
“…was more likely to be expressed in the cytoplasm of tumor cells in in the tumor. 52,53 The study demonstrated that IL-33 expression in cytoplasm of tumor was significantly and positively correlated with CD3 + /CD8 + T lymphocytes. Our results preliminarily showed that the tumor-derived IL-33 may played an antitumor role, which promote the infiltration of T lymphocytes in tumor.…”
Section: Discussionmentioning
confidence: 96%
“…Proof-of-concept is provided in clinical studies with the IL-33 antibody etokimab, and with the ST2 antibody astegolimab showing improvement in patients with atopic dermatitis [ 75 ], a peanut allergy [ 76 ], or severe asthma [ 77 ]. Therapeutic strategies for targeting IL-33/ST2 signaling for the treatment of various inflammatory diseases are evolving [ 78 , 79 ]. However, additional studies are required to establish that blocking the IL33/ST2 axis may have therapeutic potential for MCC treatment.…”
Section: Discussionmentioning
confidence: 99%